Correspondence re: Feyler et al., Point: Myeloperoxidase −463G → a polymorphism and lung cancer risk. Cancer Epidemiol. Biomark. Prev., 11: 1550-1554, 2002, and Xu et al., Counterpoint: The Myeloperoxidase −463G → a polymorphism does not decrease lung cancer susceptibility in Caucasians. 11: 1555-1559, 2002 - Dally, Heike; Bartsch, Helmut; Risch, Angela (Cancer epidemiology, biomarkers & prevention, 2003)
Since 1997, nine studies on MPO-463 genotype and lung cancer risk in Caucasians have been published. A significant reduction of the levels of benzo( a )pyrene diol epoxide-DNA adducts in human skin after coal tar treatment for MPO-A allele carriers has also been shown [(1)][1] . This indicates that